Special Space Curves Characterized by (α^(3), α^(4), α^(5)) = 0 - Saracoglu, S.; Yayli, Y. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
By using the facts that the condition(α^(1), α^(2), α^(3)) = 0 characterizes a plane curve and the condition (α^(2), α^(3), α^(4)) = 0 characterizes a curve of constant slope, we present special space curves characterized by the condition (α^(3), α^(4), α^(5)) = 0, in different approaches. It is shown that the space curve is Salkowski if and only if (α^(3), α^(4), α^(5)) = 0. The approach used in our investigation can be useful in understanding the role of the curves characterized by (α^(3), α^(4), α^(5)) = 0 in differential geometry.